Analisis Ability to Pay dan Willingness To Pay Tarif Krl terhadap Rencana Pengoperasian Krl Relasi Madiun-Solo - Safrudin Kurniawan (Syntax Corporation Indonesia, 2023)
With the planned operation of the Madiun - Solo PP KRL connection which is an extension of the Yogya - Solo KRL route which is currently operating, of course, research is needed regarding the Ability To Pay (ATP) and Willingness To Pay (WTP) of prospective passengers in paying fares which will later be applied. . This research is a descriptive quantitative study which will collect data by conducting a survey to prospective users of the Madiun – Solo KRL Relation. The results of this study indicate that the average Ability To Pay (ATP) of all respondents to pay KRL tariffs is Rp. 48,968, - while the average Willingness To Pay (WTP) of all respondents to pay KRL tariffs is Rp. 20,000. From the calculation above, it can be seen that the Ability To Pay value is greater than the Willingness To Pay value. This means that the respondent has a relatively high income but a low level of utility for the mode of transportation, such a respondent is included in the Choiced Raiders category..